2016
DOI: 10.1371/journal.pone.0150923
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low-Frequency Electromagnetic Fields Promote In Vitro Neuronal Differentiation and Neurite Outgrowth of Embryonic Neural Stem Cells via Up-Regulating TRPC1

Abstract: Exposure to extremely low-frequency electromagnetic fields (ELF-EMFs) can enhance hippocampal neurogenesis in adult mice. However, little is focused on the effects of ELF-EMFs on embryonic neurogenesis. Here, we studied the potential effects of ELF-EMFs on embryonic neural stem cells (eNSCs). We exposed eNSCs to ELF-EMF (50 Hz, 1 mT) for 1, 2, and 3 days with 4 hours per day. We found that eNSC proliferation and maintenance were significantly enhanced after ELF-EMF exposure in proliferation medium. ELF-EMF exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 58 publications
(82 reference statements)
8
58
0
1
Order By: Relevance
“…The exposure to extremely low frequency ELF-EMF (50 Hz) induced more rapid maturation and differentiation in neural cells. These included rat immature cerebellar granule neurons and mouse embryonic neural stem cells [3, 41], as well as mouse pituitary corticotrope-derived cells [42]. Similar results were obtained in human cardiac stem cells derived from human myocardial bioptic specimens, where differentiation toward a cardiac-specific phenotype was observed after exposure to low-frequency EMF [43].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The exposure to extremely low frequency ELF-EMF (50 Hz) induced more rapid maturation and differentiation in neural cells. These included rat immature cerebellar granule neurons and mouse embryonic neural stem cells [3, 41], as well as mouse pituitary corticotrope-derived cells [42]. Similar results were obtained in human cardiac stem cells derived from human myocardial bioptic specimens, where differentiation toward a cardiac-specific phenotype was observed after exposure to low-frequency EMF [43].…”
Section: Discussionmentioning
confidence: 68%
“…ELF-EMF is proven to affect differentiation in murine and human cells of different origins [3, 41-44]. The exposure to extremely low frequency ELF-EMF (50 Hz) induced more rapid maturation and differentiation in neural cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation was attributed to the topography facilitating binding between cellular integrins and ligands, which (Xie et al, 2009;Schaub and Gilbert, 2011;Wong et al, 2011;Froeter et al, 2014;Koppes et al, 2014;Lee et al, 2015b). b Electrical References: (Jaffe and Stern, 1979;Patel and Poo, 1982;Hotary and Robinson, 1991;Davenport and McCaig, 1993;Metcalf and Borgens, 1994;Yao et al, 2008Yao et al, , 2009Yao et al, , 2011Graves et al, 2011;Koppes et al, 2014;Kim et al, 2016;Ma et al, 2016). c Mechanical Stiffness References: (Balgude et al, 2001;Discher et al, 2005;Jiang et al, 2010;Keung et al, 2012;Lee et al, 2013;Zhang et al, 2014;Mosley et al, 2017).…”
Section: Topographical Cues Drive Alignment and Directionalitymentioning
confidence: 99%
“…In early development, electric potentials define migration paths of the cells and differentiation, driving the formation of the neural tube Robinson, 1990, 1991;Metcalf and Borgens, 1994;Yao et al, 2008;Ma et al, 2016). Signal transmission in neurons is mediated by ion fluxes across the cell membrane.…”
Section: Application Of Electric Fields To Manipulate Neurite Extensionmentioning
confidence: 99%
“…19 It has been reported that ELF-EMF may alter the mRNA expression levels of several genes 20,21 including the brain, 22,23 neuroblastoma cells, 24 and embryonic neural stem cells. 25,26 As there is no study published yet about investigation on the alteration of the PDYN and OPRM1 mRNA expression levels in human SH-SY5Y cells due to ELF-EMF, we designed and carried out the following experiment.…”
mentioning
confidence: 99%